Analysis of the Mature and Necessity of Virtual Education in the Present Age with Emphasis on Effective Teaching Methods in Teaching English through Virtual Education - Eskandian, Abdullah Hosseini; Nejhadian, Masoumeh Rajab (Journal of English Teaching and Learning Issues, 2021)
English language teaching in virtual environment the selection of effective and appropriate teaching methods according to the characteristics and capabilities of this type of education is one of the problems that teachers face. In reviewing and analyzing teaching methods in virtual education can help teachers to adopt effective teaching methods. This paper using descriptive-analytical method and using library resources, first the terms synonymous with virtual education and the time of origin of this type of education are presented. Then, the definitions of virtual education, methods of providing virtual education and the necessity of virtual education are discussed, and then some effective teaching methods in English virtual education are stated and analyzed and concludes with the advantages and disadvantages of virtual education. Virtual education can be considered as a kind of lifelong learning that focuses on the learner and among the effective and inclusive teaching methods in this type of training that is useful for teaching English can be problem solving, online discussion, small online groups and methods constructivism pointed out. It can be said that by using special methods, it is possible to teach English better through virtual education.